Implikasi Normatif Undang-Undang Cipta Kerja terhadap Perseroan Perorangan sebagai Reformasi Hukum Bisnis di Indonesia - Chairy, Raudhea Vara Yulfa (Indonesia Berdaya, 2023)
It is clear that Micro, Small and Medium Enterprises (MSMEs) are the most common type of business among other types of businesses, but being able to register as a Limited Liability Company legal entity is by far the most popular form of business entity in Indonesia. As a result, Law Number 11 of 2020 concerning Job Creation was passed with the aim of improving the business climate and creating the widest possible employment opportunities. This regulation stipulates a new type of company, namely a sole proprietorship company. This sole proprietorship is an expression of changing laws in Indonesia, combining world regulations and economic demands for Indonesian society. This paper aims to find out the normative implications of the Job Creation Law for individual companies as a business law reform in Indonesia. The approach used in this article is normative juridical, with the methodology of collecting literature study materials. The conclusion of this paper is that the implementation of the individual company concept as a legal entity in Indonesia opens up the possibility of establishing and owning a company by one person with a concept that takes the form of a limited liability company.